Reformasi di Kementerian Pertahanan RI - Sukadis, Beni (Jurnal Keamanan Nasional, 2016)
Defense reform still underway since Indonesia passed the Law on State Defense and the TNI the reform law has not been completed yet, because there are many factors that impede the reform process. Some of the factors are the paternalistic culture still exists in the bureaucracy, there is also ambiguity on the relations between the Defense Minister and the Commander of TNI in the division of labor especially to civil-military relations and weak civilian leadership in managing the reform at the Ministry of Defense. Until now, the implementation of civil supremacy within the Ministry is vague, although the ministers are civilian, but in fact the military domination in decision-making process remains strong. Whereas, civil supremacy should not be exemplified in the top position, but the civilians authority take the lead in the decision making in accordance to the State Policy as stipulated by the law.